2020
DOI: 10.1111/tan.13901
|View full text |Cite
|
Sign up to set email alerts
|

Rapid high‐resolution HLA genotyping by MinION Oxford nanopore sequencing for deceased donor organ allocation

Abstract: Recently, HLA epitopes on donor HLA molecules have been shown to be important in the success of solid organ transplantation. However, these epitopes can only be defined using high‐resolution typing results of which are often not available prior to deceased donor allocation. The ability to perform high‐resolution typing at all HLA loci for deceased organ donor allocation prior to transplantation would have major clinical benefits, in particular for highly sensitised recipients. We, therefore, developed a rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Earlier reported efforts to utilize the nanopore technology for HLA genotyping fell short of providing a comprehensive solution of characterizing all loci within a time frame necessary for all of our clinical needs [ 28 ]. Most recently, however, De Santis et al using a combination of a multiplex PCR and ONT reported successful characterization of all 11 HLA loci [ 29 ]. Our report introduces nanopore technology as a viable alternative to existing methods for reliable clinical HLA typing of all eleven loci within a significantly shorter time.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reported efforts to utilize the nanopore technology for HLA genotyping fell short of providing a comprehensive solution of characterizing all loci within a time frame necessary for all of our clinical needs [ 28 ]. Most recently, however, De Santis et al using a combination of a multiplex PCR and ONT reported successful characterization of all 11 HLA loci [ 29 ]. Our report introduces nanopore technology as a viable alternative to existing methods for reliable clinical HLA typing of all eleven loci within a significantly shorter time.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation may soon be resolved by third-generation sequencing, which has been reported to achieve 2F-HR typing for 11 HLA loci in 4 to 4.5 hours. 5 Time and cost have been barriers to routine use of 2F-HR typing for kidney transplantation. Commercial kits for HLA typing using next-generation sequencing (NGS) offer options for completing 2F-HR typing in 1 to 5 days.…”
Section: The Clini C Al D Ilemmamentioning
confidence: 99%
“…However, LR HLA typing can cause false‐positive virtual crossmatches, which preclude compatible transplants. This limitation may soon be resolved by third‐generation sequencing, which has been reported to achieve 2F‐HR typing for 11 HLA loci in 4 to 4.5 hours 5 …”
Section: The Clinical Dilemmamentioning
confidence: 99%
“…Initially, single-pass accuracies of only 68.4% (Phred score of 5) were reported with the MinION in 2015 [13]. Using the R9.4.1 flow cell chemistry and Guppy base caller, raw read accuracies of 85-90% have been reported [14]. This is considerably less than the 99.999% accuracy in sanger sequencing [15] and 99.92% in Illumina [16].…”
Section: Introductionmentioning
confidence: 99%